Standard handbook of powerplant engineering - Elliot, Thomas C.;Chen, Kao;Swanekamp, Robert C. (New York, NY : McGraw Hill Education, 1997)
Provides powerplant engineers with a range of information, from basic operations to leading-edge technologies, including steam generation, turbines and diesels, fuels and fuel handling, pollution control, plant electrical systems, and instrumentation and control. This title includes over 600 drawings, diagrams, and photographs.
Section I: Energy Resources for Power Generation.Overview of U.S.Energy Resources.Coal.Oil and Natural Gas.Nuclear Energy.Hydroelectric Energy.Solar Energy.Geothermal Energy.Wind Energy.Biomass Energy.Waste Fuels.Section II: Steam Powerplants.Steam Fundamentals.Basic Powerplant Design.Steam Generators.Boiler Auxiliaries.Cooling Towers and Air-Cooled Condensers.Water Treatment.Section III: Prime Movers.Steam-Turbine Fundamentals.Steam-Turbine Design.Gas-Turbine Fundamentals.Gas-Turbine Design.Hydraulic Turbines.Oil- and Gas-Fired Reciprocating Engines.Section IV: Plant Electric Systems.AC Generators and Generator Protection.Transformers and Transformer Protection.Electrical Interconnections.In-Plant Electrical Distribution.AC Motors and Their Applications.Busway Applications.Cable Applications.Section V: Instrumentation and Control.Powerplant Instruments.Combustion Control and Burner Management.Turbine and Engine Governors.Key Systems and Components.Human Engineering: Human-Machine Interface.Section VI: Nuclear Plant Systems.Introduction.Fission Theory.Nuclear Steam Supply Systems.Nuclear Plant Operation, Maintenance, and Control.Reactor Safety.Regulation.Section VII: Hydroelectric Power Stations.General Features of a Hydroelectric Project.Dams, Spillways, Water Conductors, and Powerhouses.Auxiliary Mechanical Equipment.Hydroelectric Generators, Transformers, and Controls.Section VIII: Alternative Energy Plants--Emerging Technologies.Solar Power Systems in Space.Geothermal Power Systems.Wind Energy Technology.Wood/Biomass Powerplants.Waste-Fired Plant Design.Fuel Cell Plants.Section IX: Environmental Controls.Environmental Legisation and Regulation.Air Emission Controls.Water Emission Controls.Solid Waste Management.Powerplant Noise and Its Control.Section X: Appendices: Conversion Factors.Standard Nominal System Voltages and Voltage Ranges.Abbreviations.
Includes index.
Keywords: ELECTRIC POWER-PLANTS